The Spiritual Competence Aspect in Counselling Service - Rohaizan, Baru; Mohd Shahril, Othman; Syed Hadzrullathfi, Syed Omar; W Aeshah Ameiha, Wan Ahmad (2014)
The spiritual element plays an important role in the lives of humans. Numerous problems have befallen humans due to individual misinterpretations regarding spiritual elements that have eventually brought about self-induced stress and feelings of hopelessness. Hence, the emphases on the spiritual aspect in counselling sessions will help to deal will this matter effectively. This article discusses the need to involve the counsellor’s element of spiritual competence when implementing counselling because it is related to the increase in function, competence and the mental health of the individual. Good preparation and a well-grounded spiritual competence are needed by a counsellor to implement the spiritual element more effectively during counselling sessions.